2021
DOI: 10.1371/journal.pone.0258069
|View full text |Cite
|
Sign up to set email alerts
|

Does algae β-glucan affect the fecal bacteriome in dairy calves?

Abstract: β-glucans has been reported to be associated with many health-promoting and improvements in animal performance, however, information about their effects on the bacterial community remains unknown. This study aimed to investigate how the addition of β-glucans can affect the fecal bacterial community with possible consequences on animal growth and health. For this, newborn Holstein calves (n = 14) were individually housed in tropical shelters and blocked according to sex, date, and weight at birth and randomly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 47 publications
0
7
0
1
Order By: Relevance
“…Bacteroides encodes polysaccharide binding proteins in the outer membrane through polysaccharide utilization sites (PUL) to capture polysaccharides and decompose polysaccharides into oligosaccharides to promote the utilization and uptake of dietary polysaccharides by Bacteroides (Tamura et al 2017 ). Faecalibacterium facilitates the utilization of acetate in the intestine (Virginio Junior et al 2021 ). Acetate is used as an energy source for the liver and peripheral tissues and as a signal molecule in gluconeogenesis and lipogenesis (Zambell et al 2003 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bacteroides encodes polysaccharide binding proteins in the outer membrane through polysaccharide utilization sites (PUL) to capture polysaccharides and decompose polysaccharides into oligosaccharides to promote the utilization and uptake of dietary polysaccharides by Bacteroides (Tamura et al 2017 ). Faecalibacterium facilitates the utilization of acetate in the intestine (Virginio Junior et al 2021 ). Acetate is used as an energy source for the liver and peripheral tissues and as a signal molecule in gluconeogenesis and lipogenesis (Zambell et al 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…β-glucan is considered a natural prebiotic with various biological functions, such as antioxidant, free radical scavenging, anti-tumor, anti-cancer, and immune activation, competing with pathogenic microorganisms for binding sites in intestinal epithelial cells to prevent inflammation (Baldassano et al 2017 ; De Marco et al 2021 ; Mo et al 2017 ; Virginio et al 2021 ; Xu et al 2009 ). The main chain of β-1,3/1,6-glucan is a linear skeleton with β-1,3 bonds, and the side chain is a highly branched β-1,6 bond (Baldassano et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ma et al [ 16 ] found that dietary supplementation of 75 mg/kg β-glucan increased average daily gain (ADG) and gain-to-feed ratios in calves during the milk-feeding period. Studies have reported that milk replacer supplemented with 2g of β-glucan per day are beneficial to health and growth in preweaning calve, increasing the abundance of Alloprevotella and Holdemanella in gut [ 17 ]. However, the relationship of gut microbiota-host metabolism and β-glucan supplementation in pre-weaning dairy calves remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…There are 2 common sources of bioavailable β-glucans: one is algae such as Euglena gracilis; these algae were shown to have highly water soluble portions in an in vitro study (Phillips et al, 2019). Recently, supplementation of algae β-glucans to calves promoted greater abundance of the Alloprevotella and Holdemanella genera in feces, suggesting that feeding algae β-glucans to calves may positively alter the ratio of commensal bacteria in the lower gut (Virginio Junior et al, 2021). However, to our knowledge, no study has investigated the effect of algae-derived β-glucans on calf health and performance, and this warrants investigation.…”
Section: Introductionmentioning
confidence: 99%